Guerra fría en las aulas: el canon de la teoría política contemporánea en Colombia. (2020)
This paper aimed to identify the existence of a canon of authors, schools and subjects in the teaching of contemporary political theory in the undergraduate programs of Political Sciences currently taught in Colombia. From this canon it was formulated a diagnosis of the main approaches and theories in the teaching of contemporary political theory, taking as analysis criteria the way that the canon resolve four epistemological tensions in the sub-discipline: monism vs. pluralism, local vs. global, modernity vs. post-modernity, and disciplinary vs. interdisciplinary. This analysis allowed to conclude that the canon is characterized by a pluralistic, interdisciplinary, local, and modern perspective, and demonstrates a process of redefinition of its problematic borders as well as a relatively refractory spirit to the influx of the Anglo-Saxon political theory.